AB0973 The Novel Photo Optical Imaging (LIGHTSCAN) is More Sensitive than Musculoskeletal Ultrasound and Clinical Examination in Patients with Rheumatoid Arthritis and Osteoarthritis. (10th June 2014) - Amitai, I.; Ohrndorf, S.; Werner, S.; Schicke, B.; Burmester, G.-R.; Minet, O.; Zabaryło, U.; Backhaus, M.
Abstract : Background: The Lightscan, a novel imaging technology, is detecting inflammatory activity in proximal interphalangeal (PIP) joints. Objectives: This study aimed at the comparison of Lightscan (LS) to musculoskeletal ultrasonography (US) and clinical examination (CE) in patients with rheumatoid arthritis (RA) or osteoarthritis (OA) and in healthy controls. Methods: A total of 87 subjects (70 female, mean age 49±19 years, range 22-86) were examined. The total cohort included 30 patients with active RA (DAS28>2.6), 8 RA patients in clinical remission (DAS28≤2.6), 21 patients with OA, and 28 individuals as a healthy control group. All patients received clinical joint examination (tender/swollen joints). US in grey-scale (GSUS) and power Doppler mode (PDUS) of the PIPs 2-5 (palmar/dorsal view) were performed. All patients were examined by LS. LS was transilluminating the PIPs of both hands using laser diodes with three different wavelengths (670, 820, and 904 nm), one joint after the other. A CCD camera was recording the scattered-light in a 2-dimensional light pattern. Those black/white bitmaps with a depth of 8 bits were transformed into a false colour image [1] and analysed with a non-local image segmentation method [2]. In order to compare LS with US, a sum-score was defined and calculated for GSUS, PDUS and LS individually. The means of the sum-score were compared to each other. ROC-analysis was done for LS and US. Results: In the statistical analysis the results of LS and CE agreed in 52% on average (agreement was calculated for each PIP joint individually; agreement range was 32-66%). Disagreement in 40% (range 28-55%) of the results was due to the high rate of positive findings in LS. In 8% (range 2-12.5%) positive findings were only found in CE. In the ROC-analysis, LS showed better sensitivity and specificity for the detection of inflammation in RA and OA (AUC=0.88) than GSUS (AUC=0.8) and PDUS (AUC=0.67). By using this analysis, the cut-off for LS was defined at the score of 1.3. Conclusions: It is known that US is more sensitive than the CE [3, 4]. Thus, while showing better results in the ROC-analysis, we conclude LS to be more sensitive than US and CE in assessing inflammatory activity in patients with RA and OA. References: Minet O et al. J Biophotonics. 2010;3:130-7 Minet O et al. Las. Phys. Lett. 2007;4:604-10 Backhaus, M et al. Arthritis Rheum. 1999;42:1232-45 Backhaus, M et al. Ann Rheum Dis. 2002;6:895-904 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3338